The Adverse Effects of Recruiting Non-Expert Officials - Sitti Sagirah (Farabi)
This article elaborates and analyzes the meaning of the predictive Hadith about Handing over affairs to non-experts, then criticizes its authenticity and analyzes its content and implementation in the present context. The method used is the tahli>li method and textual, intertextual, and contextual interpretation techniques with a multidisciplinary approach. Before criticizing the authenticity of the Hadith based on the rules of hadith validity, first, perform takhri>j al-hadi>s\ by using the keyword d} uyi'at al-ama>nat. After recognizing the quality of the traditions traced in this study as sahih traditions, a study of ma'a>ni> al-hadith followed. The results show that the Prophetic tradition is of sahih quality. This study shows that the predictive hadith "Handing over affairs to non-experts is a sign of the end of the world," narrated by Ahmad ibn Hanbal, in terms of quantity, is classified as a garīb hadith because the narrator's line from the level of the companion (a'lā) to the fourth level of the narrator is single. Regarding the quality of the sanad and matan, it is classified as a hasan hadith because one of the narrators, Fulaih, based on the conclusion of the assessment of the hadith critics, was not d}a>bit}. However, due to the existence of al-Bukhari's chain of transmission, the Hadith rises to the level of sahih ligairih. Thus, the Hadith has legal authority to be used as an argument (hujjah).